Identifying the Mathematical Concept Understanding Ability of Junior High School Students in Learning Linear Function Material - Valentine, Vivi Eviyanti; Tuti Alawiyah; Irmawati Liliana Kusuma Dewi; Tri Nopriana (EDUPEDIA Publisher, 2024)
Understanding mathematical and mathematical concepts is one of my fundamental abilities. Therefore, it is necessary to teach mathematics by emphasizing concept understanding so that students are trained to solve problems with the concepts they understand appropriately. This study aims to analyze the knowledge of mathematical concepts of students at junior high school level grade VIII on linear function material. This research is qualitative research with a descriptive method. The research subjects were VIII grade students, as many as 33 students. Data collection through two description questions was then analyzed according to the ability of high, medium, and low student categories. Furthermore, direct interviews were conducted to obtain more in-depth information about students' understanding of mathematical concepts. The results showed that 39.39% of students had high-category mathematical concept understanding ability (ST), 6.06% of students in the medium category (SS), and 54.55% of students in the low category (SR). ST fulfills all indicators with the correct answer, and SS fulfills all indicators, but the answers produced could be more precise. SR cannot apply concepts, so it only fulfills some indicators, which results in errors in solving problems.